Entrepreneurial self-efficacy: A study on women small-scale individual entrepreneurs at the border towns of Malaysia and Thailand - Mansor, Mohd Najib (American Scientific Publishers, 2016)
This study examined the association of demographic factors and predictable environment with entrepreneurial self-efficacy at the border towns of Malaysia and Thailand. Data from 204 Women Small-Scale Individual Entrepreneurs (WSIEs) were analyzed using multiple regression analysis. The result of this study revealed that age has shown significant relationship with the entrepreneurial self-efficacy. Interestingly, with regard to the predictable environment, there is also a positive and significant relationship between predictable environment and entrepreneurial self-efficacy. The result also shows significant relationship between entrepreneurial self-efficacy and entrepreneurial performance outcome.